Approaches for monitoring nuclear translation. - Iborra, F; Jackson, D; Cook, P (2004)
The nuclear membrane is the defining feature of eukaryotes. It divides the cell into two functionally specialized compartments, and it is widely assumed that translation is restricted to only one: the cytoplasm. However, recent results suggest that some translation takes place in nuclei closely coupled to transcription. Various labeling techniques are described that enable nascent peptides to be labeled and then localized wherever they might be in the cell.